A pan-PPAR agonist E17241 ameliorates hyperglycemia and diabetic dyslipidemia in KKAy mice via up-regulating ABCA1 in islet, liver, and white adipose tissue - Sheng, Ren; Li, Yining; Wu, Yexiang; Liu, Chang; Wang, Weizhi; Han, Xiaowan; Li, Yinghong; Lei, Lijuan; Jiang, Xinhai; Zhang, Yuyan; Zhang, Yuhao; Li, Shunwang; et al. (Biomedicine & pharmacotherapy, 2024)
Type 2 diabetes mellitus (T2DM) is a common chronic metabolic disease. Peroxisome proliferator-activated receptors (PPARs) play crucial roles in regulating glucolipid metabolism. Previous studies showed that E17241 could ameliorate atherosclerosis and lower fasting blood glucose levels in ApoE−/− mice. In this work, we investigated the role of E17241 in glycolipid metabolism in diabetic KKAy mice. We confirmed that E17241 is a powerful pan-PPAR agonist with a potent agonistic activity on PPARγ, a high activity on PPARα, and a moderate activity on PPARδ. E17241 also significantly increased the protein expression of ATP-binding cassette transporter 1 (ABCA1), a crucial downstream target gene for PPARs. E17241 clearly lowered plasma glucose levels, improved OGTT and ITT, decreased islet cholesterol content, improved β-cell function, and promoted insulin secretion in KKAy mice. Moreover, E17241 could significantly lower plasma total cholesterol and triglyceride levels, reduce liver lipid deposition, and improve the adipocyte hypertrophy and the inflammatory response in epididymal white adipose tissue. Further mechanistic studies indicated that E17241 boosts cholesterol efflux and insulin secretion in an ABCA1 dependent manner. RNA-seq and qRT-PCR analysis demonstrated that E17241 induced different expression of PPAR target genes in liver and adipose tissue differently from the PPARγ agonist rosiglitazone. In addition, E17241 treatment was also demonstrated to have an exhilarating cardiorenal benefits. Our results demonstrate that E17241 regulates glucolipid metabolism in KKAy diabetic mice while having cardiorenal benefits without inducing weight gain. It is a promising drug candidate for the treatment of T2DM. [Display omitted] •E17241, a unique pan-PPAR agonist and an ABCA1 upregulator, effectively ameliorates diabetic dyslipidemia in KKAy mice.•E17241 significantly lowers plasma fasting glucose levels and improves OGTT and ITT in KKAy mice.•E17241 improves islet function by promoting islet cholesterol efflux in an ABCA1-dependent way.•E17241 decreases liver lipid accumulation and eWAT mass by regulating PPAR target genes differently from rosiglitazone.•E17241 has cardiorenal benefits in KKAy mice.